2022
DOI: 10.1177/15423050221090864
|View full text |Cite
|
Sign up to set email alerts
|

Clergy Resilience: Accessing Supportive Resources to Balance the Impact of Role-Related Stress and Adversity

Abstract: Resilience is a helpful construct when considering how to support clergy well-being. The purpose of this study was to gain knowledge about clergy resilience, specifically those resources that clergy perceived had supported their professional resilience. The study gave attention to aspects of preservice training and professional development that helped to foster clergy resilience and initiatives that clergy desired to further support their resilience. Clergy reported multiple resources that supported their resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This article reports on the findings related to types of adversity clergy reported, arising from the qualitative data collection. Other study findings are reported elsewhere, including the results from the quantitative well-being and resilience scale (Clarke et al, 2022a), findings related to the resources that clergy identified as supporting their resilience (Clarke et al, 2022b), and the Clergy Resilience Model (forthcoming).…”
Section: The Purpose Of This Studymentioning
confidence: 88%
“…This article reports on the findings related to types of adversity clergy reported, arising from the qualitative data collection. Other study findings are reported elsewhere, including the results from the quantitative well-being and resilience scale (Clarke et al, 2022a), findings related to the resources that clergy identified as supporting their resilience (Clarke et al, 2022b), and the Clergy Resilience Model (forthcoming).…”
Section: The Purpose Of This Studymentioning
confidence: 88%
“…Furthermore, aspects related to the overarching influence of key spiritual factors on clergy resilience (Clarke, 2021; Clarke et al, 2022a) were also incorporated into the global meaning aspect of the model. In considering spiritual life supportive resources, Clarke (2021) considered some aspects of this category to have a higher-level influence on clergy resilience, through the appraisal processes and global meaning.…”
Section: Clergy Resilience Modelmentioning
confidence: 99%
“…The Clergy Resilience Model also highlights the importance of spiritual meaning in the global appraisal system of the clergy member. Theological beliefs, calling to ministry, and partnership with God impacted how clergy interpreted adversity and how they viewed resources (Clarke, 2021, Clarke et al, 2022a, 2022b). These findings point to an appraisal system that governs the global meaning given to situational events.…”
Section: Clergy Resilience Modelmentioning
confidence: 99%
See 2 more Smart Citations